Custom human endogenous retroviruses dedicated microarray identifies self-induced HERV-W family elements reactivated in testicular cancer upon methylation control - Gimenez, Juliette; Montgiraud, Cécile; Pichon, Jean-Philippe; Bonnaud, Bertrand; Arsac, Maud; Ruel, Karine; Bouton, Olivier; Mallet, François (Nucleic acids research, 2010)
Endogenous retroviruses (ERVs) are an inherited part of the eukaryotic genomes, and represent ~400 000 loci in the human genome. Human endogenous retroviruses (HERVs) can be divided into distinct families, composed of phylogenetically related but structurally heterogeneous elements. The majority of HERVs are silent in most physiological contexts, whereas a significant expression is observed in pathological contexts, such as cancers. Owing to their repetitive nature, few of the active HERV elements have been accurately identified. In addition, there are no criteria defining the active promoters among HERV long-terminal repeats (LTRs). Hence, it is difficult to understand the HERV (de)regulation mechanisms and their implication on the physiopathology of the host. We developed a microarray to specifically detect the LTR-containing transcripts from the HERV-H, HERV-E, HERV-W and HERV-K(HML-2) families. HERV transcriptome was analyzed in the placenta and seven normal/tumoral match-pair samples. We identified six HERV-W loci overexpressed in testicular cancer, including a usually placenta-restricted transcript of ERVWE1. For each locus, specific overexpression was confirmed by quantitative RT-PCR, and comparison of the activity of U3 versus U5 regions suggested a U3-promoted transcription coupled with 5'R initiation. The analysis of DNA from tumoral versus normal tissue revealed that hypomethylation of U3 promoters in tumors is a prerequisite for their activation.